Chlorhexidine – mechanism of action and its application to dentistry - Łukomska-Szymańska, Monika; Sokołowski, Jerzy; Łapińska, Barbara (Journal of Stomatology, 2017)
Introduction: Chlorhexidine (CHX) is considered the most effective and safe antimicrobial substance used in dentistry. Aim of the study: To present chlorhexidine’s mechanism of action and summarize its therapeutic use in dentistry. Conclusions: Chlorhexidine is used mainly in salt forms: diacetate, digluconate and dihydrochloride. Chlorhexidine shows activity against bacteria Gram positive, Gram negative, aerobic and facultative anaerobic as well as against viruses, yeasts and fungi. CHX lowers the amount of S. mutans in saliva and dental plaque, and also shows stronger bactericidal activity against E. faecalis in dentinal tubules than calcium hydrochloride. CHX can be chemisorbed on the surface of dental hydroxyapatite or can react, as ion, producing insoluble compounds with phosphate ions, that are present in dental plaque, saliva and hydroxyapatite. Afterwards, chlorhexidine can be released, without influencing bonding between enamel and dentin to resin composite filling material. CHX exhibits low harmfulness and basically no toxic activity. Chlorhexidine and its derivatives (mainly digluconate), as solutions, are used in endodontic, periodontic and implantoprosthetic treatment. CHX is also used as disinfectant before dental cavity filling as well as component of adhesive systems and resin based restorative materials. Given its wide spectrum of antimicrobial activity, chlorhexidine is still an important issue in research on new materials and restoration techniques used in reconstructive dentistry.